2010
DOI: 10.1017/s030500090999050x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the contribution of phonotactic cues to the problem of word segmentation

Abstract: How do infants find the words in the speech stream? Computational models help us understand this feat by revealing the advantages and disadvantages of different strategies that infants might use. Here, we outline a computational model of word segmentation that aims both to incorporate cues proposed by language acquisition researchers and to establish the contributions different cues can make to word segmentation. We present experimental results from modified versions of Venkataraman's (2001) segmentation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 34 publications
4
52
0
Order By: Relevance
“…Similarly, phonotactic constraints differ between languages, with legal words in one language being illegal in others. Thus, one would normally assume that in order to use these cues, infants must have already learned some of the words in the language in order to identify the dominant stress patterns and phonotactics [though see Blanchard et al (2010) for one way language-specific phonotactics might be learned at the same time the initial segmentation problem is being solved]. Since the point of word segmentation is to identify words in the first place, needing to know words in order to learn segmentation cues creates a chicken-and-egg problem.…”
Section: Statistical Word Segmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, phonotactic constraints differ between languages, with legal words in one language being illegal in others. Thus, one would normally assume that in order to use these cues, infants must have already learned some of the words in the language in order to identify the dominant stress patterns and phonotactics [though see Blanchard et al (2010) for one way language-specific phonotactics might be learned at the same time the initial segmentation problem is being solved]. Since the point of word segmentation is to identify words in the first place, needing to know words in order to learn segmentation cues creates a chicken-and-egg problem.…”
Section: Statistical Word Segmentationmentioning
confidence: 99%
“…Using a sliding window of a fixed length, two "voting experts" use accumulated entropy knowledge to vote whether a boundary should be inserted between two phonemes; if the number of votes exceeds a pre-determined threshold, the learner inserts a word boundary. Blanchard et al (2010) created PHOCUS (PHOnotactic CUe Segmenter), an online learner that couples statistical word learning with phonotactic constraints. In particular, Blanchard et al demonstrate a way in which language-specific phonotactic constraints, realized as likely and unlikely phonemic sequences, can be learned at the same time that segmentation is being attempted and an explicit lexicon is built.…”
Section: Bootstrap Voting Expertsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational work has shown that phonotactic constraints are learnable from transcriptions of continuous speech, and that such constraints have a positive effect on word segmentation (Adriaans & Kager, 2010;Blanchard et al, 2010;Brent & Cartwright, 1996;Cairns et al, 1997;Daland & Pierrehumbert, 2011). Phonotactic constraints might thus arise before the lexicon is in place, in particular from co-occurrence probabilities in continuous speech.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, experimental evidence suggests that infants can leverage language-independent probabilistic cues to identify that initial seed pool of words (Saffran, Aslin, & Newport, 1996;Aslin, Saffran, & Newport, 1998;Thiessen & Saffran, 2003;Pelucchi, Hay, & Saffran, 2009). This had led to significant interest in the early probabilistic segmentation strategies infants use (Brent, 1999;Batchelder, 2002;Goldwater et al, 2009;Blanchard, Heinz, & Golinkoff, 2010;Pearl et al, 2011;Lignos, 2011).…”
Section: Speech Segmentation Strategiesmentioning
confidence: 99%